Polychromatic energy‐dispersive neutron diffraction at a continuous source. (5th August 2013) - Simmons, Jason M.; Cook, Jeremy C.; Ibberson, Richard M.; Majkrzak, Charles F.; Neumann, Dan A.
<x xml:space="preserve">Abstract</x> A design for a continuous source, polychromatic beam powder neutron diffractometer based on an energy‐dispersive detection methodology is proposed. Such an instrument would offer significantly higher incident neutron flux, with an attendant increase in data collection rate, reducing the time per scan from hours to seconds. Completely passive components are conceived for neutron bandwidth shaping, and detection is achieved using a massively parallel analyzer/detector system, making installation and operation of the instrument comparatively simple. The proposed instrument is intended to be used for rapid structural characterizations of small samples or for kinetic studies of materials undergoing structural or magnetic phase changes.